Implementation of the Da'wah Management Function in the Marriage Guidance Program at the Religious Affairs Office (KUA) of Simpang Kiri District, Subulussalam City: Implementation of the Da'wah Management Function in the Marriage Guidance Program at the Religious Affairs Office (KUA) of Simpang Kiri District, Subulussalam City - Ramadhan, Rohmi; Kustiawan, Winda (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Marriage guidance is a social service process in the form of providing knowledge to prospective husband and wife before marriage, so that they become a prosperous family and can contribute effectively to the development of the nation, religion and state. The marriage guidance is encouraged and implemented by the Religious Affairs Office throughout Indonesia, especially by the KUA Simpang Kiri, Subulussalam City. This study aims to understand the implementation of the function of da'wah management in the marriage guidance program at the Religious Affairs Office (KUA) of Simpang Kiri District, Subulussalam City. This research is a qualitative research. Qualitative research is research that obtains descriptive data in written or spoken words through individuals and behavior that can be studied not in numbers or statistical processing. The data collection techniques used by the author are: observation, interviews, and documentation. The results of the study indicate that in Simpang Kiri, Subulussalam City, it plays an active role in providing pre-marital guidance services to the community, starting from the registration stage to the marriage contract process and post-marriage. This is done with the aim of being able to help each prospective bride and groom in preventing problems in the future. The implementation of the da'wah management function in the marriage guidance program at the KUA Simpang Kiri District is: First, regarding the planning in the marriage guidance program which as a whole has been in accordance with the theory and rules that have been set. Second, the success of the implementation of the organization which is marked by the application of the principle of organization. Third, the implementation of marriage guidance that runs according to plan, and pays attention to the steps of mobilization, although there are still obstacles during the implementation. Fourth, control, supervision and evaluation of da'wah are carried out so that the guidance program always runs as it should to achieve its goals